Morphological Representation of C1q in the Aging Central Nervous System - Rupprecht, Christian; Sarker, Rim S. J.; Rammes, Gerhard (Pharmacopsychiatry, 2022)
Introduction The complement protein C1q is essential for the innate immune system and neurophysiological and neuropathological processes. To gain more insight into these functions in the CNS, a comprehensive understanding of the morphological representation, especially of its cellular and subcellular target structures, is of great importance.Methods For a free-floating preparation, the brains of wild-type and ArcAβ mice were cut into 100 μm slices. Living slices were incubated in Ringer’s solution and then fixed in 4% paraformaldehyde (PFA) and stained with different primary and secondary antibodies or methoxy-X04.Results C1q was abundant in the entire brain. Interestingly, C1q accumulated around cell nuclei, with a perineuronal localization around neuronal somata and a paraneuronal accumulation around non-neuronal cells, e. g., microglia. Moreover, dendritic-like, linear, branched C1q signals were observed in the area between the dentate gyrus and the CA1 region of the hippocampus. Complementary staining revealed an overlap with β-amyloid accumulation reflected by the deposition of C1q within plaques and modified basal C1q levels in the brains of transgenic ArcAβ animals.Discussion The applied free-floating approach is suitable for C1q immunofluorescence imaging. The consistent colocalization of the complement protein C1q with β-amyloid plaques may reflect an activated immune response, whereas the accumulation of C1q around neuronal structures such as somata and dendrites is still a matter of debate. Intriguingly, C1q surrounds those structures in older brains of both wild-type and ArcAβ mice. Our results also indicate an involvement of C1q in neurophysiological and neurodegenerative processes.
Keywords: C1q, Synaptic pruning, neuroinflammation, Alzheimer’s disease, neurodegeneration